Knowledge, attitude, and perception about the utilization of dental services during COVID-19 pandemic among the general population: A cross-sectional survey of an indian subpopulation - Sivagami Nachiyar; Subha Anirudhan; Vineetha Chakravarthy; Ambalavanan Parthasarathy; Minu Koshy; Hari Baskar (Wolters Kluwer Medknow Publications, 2022)
Background: The impact of the COVID-19 pandemic made many countries impose lockdown, movement control, or "shelter in place" orders on their residents. The effectiveness of these mitigation measures is highly dependent on the cooperation and compliance of all the members of the population. Many patients were observed to approach dental hospitals and clinics for nonemergency procedures without understanding the risk of contracting the disease.Aim: The aim of this study was to assess the knowledge and attitude about the utilization of dental services during the peak of pandemic.Materials and Methods: An online questionnaire survey was prepared, and answers were collected from 355 participants residing in Tamil Nadu. Results: A total of 355 respondents were included in this preliminary report, and the mean knowledge score was 65.37%. The attitude of most respondents toward instituted preventive measures was satisfactory, with an average attitude score of 71.78%. Conclusion: The majority of the respondents had satisfactory knowledge of the disease, but the knowledge about the spread of infection from the dental office was deficient.